Adsorbent disposal method

Heating adsorbents to 500°C or higher enables efficient disposal by stabilizing the adsorbent and preventing ion elution, addressing the challenges of high-temperature treatments and alkaline aids in existing methods.

JP2025071207AInactive Publication Date: 2025-05-02TOSOH CORP

Patent Information

Application Number
JP2025025172
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-21
Filing Date
2025-02-19
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for disposing of adsorbents used in treating hazardous ions in water require high temperatures exceeding 1000°C or the use of strong alkaline melting aids, leading to thermal deterioration, corrosion, and volatilization of the adsorbate.

Method used

A method involving heating the adsorbent to a temperature of 500°C or higher, allowing for amorphization and recrystallization at lower temperatures, thus eliminating the need for high-temperature treatments or strong alkaline aids.

Benefits of technology

This method stabilizes the adsorbent, preventing volatilization and ion elution, while simplifying the disposal process and reducing the risk of thermal degradation and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071207000006
    Figure 2025071207000006
  • Figure 2025071207000007
    Figure 2025071207000007
  • Figure 2025071207000008
    Figure 2025071207000008
Patent Text Reader

Abstract

To provide an adsorbent disposal method that is a simple method without using high-temperature processing of more than 1000°C and a strong-alkali melting aid, for achieving stabilization in a state where no volatilization and re-dissolution occurs.SOLUTION: Provided is an adsorbent disposal method including a step of heating an adsorbent that has adsorbed an adsorbate, at a temperature of 500°C or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for the disposal of adsorbents, and more particularly to a method for the disposal of adsorbents using a composition containing a silicotitanate having a sitinakite structure. The method for the disposal of adsorbents of the present invention is useful for the treatment of harmful ions in, for example, polluted water, seawater, and groundwater. [Background technology]

[0002] Inorganic ion exchangers such as silicotitanates and zeolites are known as adsorbents capable of removing harmful ions from aqueous solutions. However, if proper disposal is not performed, there is a problem that after adsorbing harmful ions, they come into contact with other metals and ions, causing reverse exchange, and the adsorbed substances are eluted. In addition, there is a problem that the adsorbed substances are desorbed and volatilized when exposed to high temperatures after treatment. For this reason, disposal treatments such as amorphization to eliminate the original crystal structure and recrystallization into another stable structure are necessary, but these treatments require high temperatures of, for example, over 1000°C or treatments using a melting aid that exhibits strong alkali, and there are problems such as thermal deterioration of the equipment, corrosion, and volatilization of the adsorbed substances.

[0003] Patent Document 1 discloses niobium-containing silicotitanate as an ion exchanger for removing radioactive materials from seawater and a method for producing the same. Patent Document 1 also discloses the results of adsorption and removal of cesium and strontium. However, it does not disclose a method for disposing of the adsorbent.

[0004] Patent Document 2 discloses a waste treatment method in which sodium borate is mixed as a melting aid with the zeolite adsorbent after adsorption, and then the adsorbent is melted at a temperature within the range of 1000 to 1100°C, and then cooled and solidified. However, a step of mixing the melting aid is required, and a high temperature of 1000°C or higher is also required. Therefore, an apparatus made of expensive materials with high heat resistance is required, and there is a risk that the adsorbed material will volatilize due to the high temperature.

[0005] Patent Document 3 describes a waste treatment method in which an alkali silicate melting aid is added to a crystalline silicotitanate adsorbent after adsorption, melted at 1100°C, and then cooled and solidified. However, as in Patent Document 1, a temperature of 1000°C or higher is required, and solidification is insufficient without a melting aid. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-170440 A [Patent Document 2] Patent No. 6157857 [Patent Document 3] Patent No. 6557416 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a method that is simpler than the conventional waste treatment method for ion adsorbents. Specifically, since decrystallization and recrystallization can be performed at a lower heating temperature than conventional methods, a highly heat-resistant device is not required and the adsorbed material is less likely to volatilize. In addition, since the use of a melting aid is not essential, the process can be simplified. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the present inventors have found a method for easily disposing of an adsorbent, and have completed the present invention. That is, the present invention is a method for disposing of an adsorbent, which is characterized by comprising a step of heating the adsorbent having adsorbed substances therein at a temperature of 500° C. or higher. Effect of the Invention

[0009] The method for waste disposal of an adsorbent of the present invention can stabilize the adsorbent to a state where there is no volatilization or re-elution, using a simple method that does not involve high-temperature treatment exceeding 1000° C. or the use of a strong alkaline melting aid. In particular, since the silicotitanate composition contained in the adsorbent is easily amorphized and recrystallized at low temperatures, the adsorbent can be disposed of in a stabilized state where there is no elution of ions due to back exchange, while suppressing corrosion of the device, thermal deterioration, and desorption due to volatilization of the adsorbed matter.

[0010] Furthermore, since the silicotitanate composition has a particularly high adsorption performance for Cs and Sr, this can be carried out after adsorption of Cs and Sr. [Brief description of the drawings]

[0011] [Figure 1] 1 shows an XRD diagram of a silicotitanate composition (adsorbent) calcined at 110° C. [Diagram 2] FIG. 1 shows XRD patterns of the silicotitanate compositions (adsorbents) of Examples 1 to 3 and Comparative Example 1 after heating. [Diagram 3] 1 shows XRD patterns of the silicotitanate molded bodies of Examples 4 to 6 and Comparative Example 2 after heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] The present invention relates to a method for waste treatment of an adsorbent, which comprises a step of heating the adsorbent that has adsorbed a substance therein at a temperature of 500° C. or higher.

[0014] By carrying out a heating process at a temperature of 500°C or higher, amorphization and recrystallization progress, and the adsorbate can be fixed, so that the adsorbate can be disposed of without elution. If the temperature is less than 500°C, amorphization is insufficient, and elution of the adsorbate occurs due to ion exchange. Here, the heating process at a temperature of 500°C or higher refers to, for example, a baking process at a temperature of 500°C or higher. In order to suppress volatilization and desorption of the adsorbate, it is preferable to heat at a temperature of 500°C or higher and 990°C or lower. It is more preferable to heat at a temperature of 500°C or higher and 800°C or lower, and even more preferable to heat at a temperature of 500°C or higher and 600°C or lower.

[0015] The adsorbent to be used in the waste treatment method of the present invention is not particularly limited as long as it adsorbs the adsorbate, and examples thereof include those containing a silicon titanate composition, an aluminosilicate composition (zeolite), a ferrosilicate composition, etc. Among these, those containing a silicon titanate composition are preferred because they are prone to amorphization at low temperatures.

[0016] Since the silicotitanate composition can be made amorphous at a lower temperature, it is preferable that the composition contains a silicotitanate having a sitinakite structure and niobium, and has diffraction peaks at least at 2θ=27.8±0.5° and 2θ=29.4±0.5°. It is also preferable that the composition has the following molar ratios and has the 2θ and XRD peak intensity ratios shown in Table 1 below.

[0017] Si / Ti molar ratio: 0.40 or more, 2.0 or less M / Ti molar ratio: 0.50 or more, 4.0 or less Nb / Ti molar ratio: 0.35 or more, 0.60 or less (M is one alkali metal selected from the group consisting of Li, Na, and K).

[0018] [Table 1] (In Table 1, the XRD peak intensity ratio refers to the ratio of peak heights.) In order to facilitate amorphization at low temperatures, the silicotitanate composition preferably contains a crystalline substance having diffraction peaks at at least 2θ=27.8±0.5° and 2θ=29.4±0.5°. Examples of the crystalline substance include silicotitanate having a vinogradovite structure and silicotitanate having a sitinakite structure, and the like. In order to facilitate amorphization at low temperatures, it is preferable to contain silicotitanate having a vinogradovite structure.

[0019] Examples of the adsorbent that can be adsorbed include strontium and cesium.

[0020] The ion exchange capacity after firing is preferably 10% or less, more preferably 5% or less, and even more preferably 1% or less. By lowering the ion exchange capacity after firing, it is possible to suppress the elution of adsorbed substances due to reverse ion exchange.

[0021] In addition to the step of heating at a temperature of 500°C or higher, the waste treatment method of the present invention may also include a step of mixing the adsorbent with a melting aid such as an alkaline substance and a solidifying agent such as cement or glass, a step of fixing the adsorbent by shaping it, and a step of cooling the adsorbent after heating.

[0022] Therefore, by subjecting the adsorbent to heat treatment at a temperature of 500°C or higher, it can be disposed of without re-elution. Because it can be stabilized at a lower temperature than conventional methods, it can be treated using equipment that is not highly heat-resistant, and volatilization of the adsorbed material can also be suppressed.

[0023] The silicotitanate composition used in the present invention will be described below.

[0024] The silicotitanate composition used in the present invention preferably contains niobium and a silicotitanate having a sitinakite structure, and has diffraction peaks at least at 2θ=27.8±0.5° and 2θ=29.4±0.5°.

[0025] In this specification, 2θ is the value (°) of the X-ray diffraction angle in a powder X-ray diffraction (hereinafter also referred to as "XRD") pattern using CuKα radiation (wavelength λ=1.5405 Å) as a radiation source. Furthermore, having a diffraction peak at 2θ means a diffraction peak in an XRD pattern obtained by measurement using the above-mentioned radiation source.

[0026] The silicotitanate composition used in the present invention contains silicotitanate having a stinakite structure and has a large adsorption amount of Cs. Furthermore, the silicotitanate composition has a large adsorption amount of Sr and Cs in the presence of seawater components, and has the effect of selectively adsorbing Sr.

[0027] A silicotitanate having a sitinakite structure (hereinafter also referred to as "S-type silicotitanate") is a crystalline silicotitanate having a crystal structure identified by the XRD peaks listed for sitinakite in the American Mineralogist Crystal Structure Database (http: / / ruff.geo.arizona.edu. / AMS / amcsd.php, search date: July 1, 2014, hereinafter referred to as the "Reference HP").

[0028] The silicotitanate composition used in the present invention contains S-type silicotitanate and niobium, and has diffraction peaks at least at 2θ=27.8±0.5° and 2θ=29.4±0.5°. By having these diffraction peaks, the silicotitanate composition of the present invention has higher Sr adsorption properties.

[0029] The state of niobium in the silicotitanate composition used in the present invention is not particularly limited as long as it contains niobium in the composition.For example, niobium may be any of the group consisting of niobium-containing compounds, niobate, niobium silicate, niobium titanate and Nb-Si-Ti oxide.In addition, niobium may be contained in S-type silicotitanate.

[0030] The silicotitanate composition used in the present invention has at least the 2θ and XRD peak intensity ratio shown in Table 2. When the silicotitanate composition has such 2θ and XRD peak intensity ratio, the silicotitanate composition used in the present invention has higher Sr adsorption properties.

[0031] [Table 2] In addition, the XRD peak intensity ratio in Table 2 is a relative value of the intensity of the XRD peak at each 2θ to the peak intensity at 2θ=11.3±0.5, where the peak intensity at 2θ=100.

[0032] The silicotitanate composition used in the present invention is a silicotitanate composition containing a crystalline substance having diffraction peaks at 2θ=27.8±0.5° and 2θ=29.4±0.5° (hereinafter also simply referred to as "crystalline substance A") and S-type silicotitanate. Here, as the crystalline substance A, at least one of the group consisting of crystalline silicotitanate other than S-type silicotitanate, titanate, niobate, silicate, niobium silicate, niobium titanate, and Nb-Si-Ti oxide can be mentioned, preferably crystalline silicotitanate other than S-type silicotitanate, more preferably silicotitanate having a vinogradovite structure (hereinafter also referred to as "V-type silicotitanate"). The V-type silicotitanate is a crystalline silicotitanate having an XRD peak corresponding to that of vinogradovite in the American Mineralogist Crystal Structure Database (http: / / ruff.geo.arizona.edu. / AMS / amcsd.php, search date: March 20, 2015). The V-type silicotitanate has characteristic XRD peaks at least at 2θ=27.8±0.5° and 2θ=29.4±0.5°.

[0033] When the silicotitanate composition used in the present invention contains an S-type silicotitanate and a crystalline silicotitanate other than S-type silicotitanate (hereinafter also referred to as a "non-S-type silicotitanate"), the silicotitanate composition may contain an S-type silicotitanate and a non-S-type silicotitanate, and may be at least one of a mixture of an S-type silicotitanate and a non-S-type silicotitanate, or a silicotitanate consisting of a mixed crystal of an S-type silicotitanate and a non-S-type silicotitanate.

[0034] The Nb / Ti molar ratio of the silicotitanate composition used in the present invention is 0.35 or more and 0.60 or less. In order to have a higher Sr adsorption performance, the Nb / Ti molar ratio is preferably 0.35 or more and 0.50 or less, or 0.40 or more and 0.60 or less.

[0035] The M / Ti molar ratio of the silicotitanate composition used in the present invention is preferably 0.50 or more and 4.0 or less, more preferably 0.50 or more and 3.0 or less, even more preferably 1.00 or more and 3.0 or less, and even more preferably 1.36 or more and 3.0 or less. By having the M / Ti molar ratio of the silicotitanate composition be 0.50 or more and 4.0 or less, the silicotitanate composition has a higher Sr adsorption performance.

[0036] The Si / Ti molar ratio of the silicotitanate composition used in the present invention is preferably 0.40 or more and 2.0 or less, further 0.50 or more and 1.8 or less, further 0.60 or more and 1.60 or less, or further 0.74 or more and 1.20 or less. By having the Si / Ti molar ratio of the silicotitanate composition of 0.40 or more and 2.00 or less, the silicotitanate composition of the present invention has a higher Sr adsorption performance.

[0037] The silicotitanate composition used in the present invention preferably has high Sr adsorption properties.

[0038] The silicotitanate composition used in the present invention can be used as a molded body (silicotitanate molded body) containing the silicotitanate composition and an inorganic binder. By being a molded body, the strength of the silicotitanate composition of the present invention is improved, and in particular, the wear resistance is excellent. Therefore, for example, even if a liquid is used as a medium to be treated and the molded body containing the silicotitanate composition of the present invention and the molded body containing the inorganic binder are continuously passed through the packed bed of the adsorbent, the wear of the molded body is suppressed, and the adsorbent can be used for a long period of time.

[0039] When the silicotitanate composition used in the present invention is a molded body, the preferred inorganic binder contained in the molded body can be, for example, at least one of the group consisting of clay, silica sol, alumina sol and zirconia sol.Moreover, the preferred inorganic binder can be clay.Moreover, the preferred clay can be at least one of the group consisting of kaolin, sepiolite and apatargite.

[0040] When the silicotitanate composition used in the present invention is a molded body, preferred thickeners contained in the molded body include, for example, water-soluble or water-insoluble cellulose such as carboxylmethylcellulose (hereinafter also referred to as CMC), hydroxycellulose, hydroxypropylmethylcellulose, hydroxypropylcellulose, ethylcellulose, and cellulose nanofiber; guar gum derivatives such as guar gum and hydroxypropylguar gum; polysaccharides such as xanthan gum, welan gum, and gellan gum belonging to biogums; polyethyleneimine derivatives; polyvinylvinylidone (hereinafter also referred to as PVP); alcohols such as glycerin, polyvinyl alcohol, and ethylene glycol derivatives; cationic, anionic, or nonionic surfactants; aqueous urethane; and polyacrylic acid derivatives, which may be used alone or in combination of two or more. The CMC may be sodium carboxymethylcellulose (hereinafter also referred to as Na-CMC). Furthermore, preferred thickeners include Na-CMC and hydroxypropylcellulose.

[0041] When the silicotitanate composition used in the present invention is a molded article, its shape can be at least one selected from the group consisting of spherical, approximately spherical, elliptical, cylindrical, polyhedral and amorphous.

[0042] When the silicotitanate composition used in the present invention is a molded article, the size thereof preferably has a diameter of 0.1 mm or more and 2.0 mm or less.

[0043] When the silicotitanate composition used in the present invention is a molded body, a manufacturing method including a molding step of kneading the silicotitanate composition of the present invention with an inorganic binder, and then molding the kneaded mixture, and a firing step of firing the molded body obtained in the molding step, can provide a silicotitanate molded body containing the silicotitanate composition and an inorganic binder.

[0044] In the molding step, at least one of a molding aid and water may be used as appropriate to improve the moldability of the kneaded product. A preferred molding aid is carboxymethyl cellulose.

[0045] In the calcination step, the temperature at which the molded body is calcined can be 100°C or higher and 400°C or lower. When the calcination temperature is 100°C or higher, the strength of the resulting molded body is further improved. When the calcination temperature is 400°C or lower, the adsorption performance can be maintained. The calcination temperature is preferably 300°C or lower, and more preferably 200°C or lower.

[0046] The silicotitanate composition used in the present invention can be used as an adsorbent for Cs. When the silicotitanate composition used in the present invention is used as an adsorbent for Cs, the adsorbent only needs to contain the silicotitanate composition, and only needs to contain at least one of a silicotitanate composition powder or a shaped body of the silicotitanate composition. Furthermore, the Cs adsorbent used in the present invention may contain at least one of the group consisting of ion exchange resins, clay minerals, zeolites, ferrocyanide compounds, and metal organic complexes.

[0047] The silicotitanate composition used in the present invention has excellent Sr adsorption performance, so it can also be used as an adsorbent for Sr. When the silicotitanate composition used in the present invention is used in a method for adsorbing at least one of Cs and Sr, the silicotitanate composition can be brought into contact with a medium to be treated that contains at least one of Cs and Sr. The medium to be treated can be at least one of liquid and solid, such as soil, waste, seawater, or groundwater. The state in which the silicotitanate composition is in contact with the medium to be treated for 24 hours or more can be regarded as adsorption equilibrium.

[0048] The silicotitanate composition used in the present invention selectively adsorbs Cs even when it is in contact with a medium to be treated that contains one or more metal ions other than Cs. Therefore, the silicotitanate composition of the present invention can be used for the adsorption treatment of Cs not only for a medium to be treated that contains Cs, but also for a medium to be treated that contains one or more metal ions other than Cs.

[0049] In the method for adsorbing at least one of Cs and Sr using the silicotitanate composition of the present invention, the temperature of the system containing the silicotitanate composition and the medium to be treated can be -30°C or higher and 60°C or lower, or even 0°C or higher and 50°C or lower, or even 10°C or higher and 30°C or lower, or even 20°C or higher and 30°C or lower. If the temperature of the system is within the above range, the silicotitanate composition of the present invention has sufficient Cs and Sr adsorption properties.

[0050] The silicotitanate composition used in the present invention adsorbs both Cs and Sr even when it is contacted with a medium containing Cs and Sr. Furthermore, the silicotitanate composition of the present invention selectively adsorbs both Cs and Sr even when it is contacted with a medium containing one or more metal ions other than Cs and Sr. Therefore, the silicotitanate composition of the present invention can be used not only for a medium containing Cs and Sr, but also for a medium containing one or more metal ions other than Cs and Sr.

[0051] The silicotitanate composition used in the present invention can be used as an adsorbent for at least one of Cs and Sr. The silicotitanate composition used in the present invention can be used in a method for adsorbing at least one of Cs and Sr.

[0052] The method for producing the silicotitanate composition used in the present invention is described below.

[0053] The method for producing a composition containing a silicotitanate having a sitinakite structure includes a gelling step of mixing an inorganic titanium compound, an inorganic silicon compound, water, and an alkali metal hydroxide to obtain a silicotitanate gel, and a crystallization step of crystallizing the silicotitanate gel.

[0054] In the gelling process, an inorganic titanium compound, an inorganic silicon compound, water, and an alkali metal hydroxide are mixed to obtain an amorphous silicotitanate gel.

[0055] In the gel process, an inorganic titanium compound is used as the titanium source, and an inorganic silicon compound is used as the silicon source. These titanium and silicon sources do not contain any hazardous or deleterious substances, including organic alkoxy metal compounds. Furthermore, the inorganic titanium compounds and inorganic silicon compounds are soluble in an aqueous alkali metal hydroxide solution. Furthermore, even if an inorganic titanium compound and an inorganic silicon compound are mixed, organic substances such as alcohol are not generated. Therefore, the titanium and silicon sources are easier to handle than organic alkoxy metal compounds such as organic alkoxy titanium compounds or organic alkoxy silicon compounds. Furthermore, because they are inexpensive, the inorganic titanium compounds and inorganic silicon compounds are more suitable for industrial use.

[0056] The inorganic titanium compound may be at least one selected from the group consisting of titanium sulfate, titanium oxysulfate, sodium metatitanate, and titanium chloride. More preferred inorganic titanium compounds include at least one of titanium sulfate and titanium oxysulfate, and more preferred inorganic titanium compounds include titanium oxysulfate.

[0057] The inorganic silicon compound may be at least one of the group consisting of sodium silicate, silica sol, fumed silica, and white carbon.Because it is relatively easy to dissolve in the aqueous solution of alkali metal hydroxide, the inorganic silicon compound is preferably at least one of sodium silicate and silica sol, and more preferably sodium silicate.

[0058] The alkali metal hydroxide may be at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. Since it is inexpensive, the alkali metal hydroxide is preferably at least one of sodium hydroxide and potassium hydroxide, and is preferably sodium hydroxide.

[0059] The water may be the moisture contained in an aqueous solution of each of the raw materials, or water may be added separately to each of the raw materials and mixed.

[0060] In the gelling process, an amorphous silicotitanate gel (hereinafter also simply referred to as "silicotitanate gel") is generated by mixing an inorganic titanium compound, an inorganic silicon compound, water, and an alkali metal hydroxide. It is preferable to mix the inorganic titanium compound, the inorganic silicon compound, water, and the alkali metal hydroxide to have the following molar ratio:

[0061] Si / Ti molar ratio: 0.5 or more, 2.0 or less H2O / Ti molar ratio: 20 or more, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less (M is one alkali metal selected from the group consisting of Li, Na, and K, and M is preferably Na). Further, the mixing molar ratio is more preferably as follows:

[0062] Si / Ti molar ratio: 1.0 or more, 2.0 or less H2O / Ti molar ratio: 20 or more, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less (M is one alkali metal selected from the group consisting of Li, Na, and K, and M is preferably Na). The Si / Ti molar ratio may be 0.5 or more and 2.0 or less, preferably 0.8 or more and 1.7 or less, more preferably 1.0 or more and 1.5 or less. By having the Si / Ti molar ratio of 0.5 or more and 2.0 or less, the silicotitanate composition can be efficiently obtained.

[0063] The H2O / Ti molar ratio is preferably 20 or more and 150 or less, more preferably 40 or more and 100 or less. When the H2O / Ti molar ratio is 20 or more, the viscosity of the obtained silicotitanate gel is reduced and the gel is easy to stir. When the H2O / Ti molar ratio is 150 or less, the yield of the silicotitanate composition is likely to be high.

[0064] The M / Ti molar ratio is preferably 1.0 or more and 5.0 or less, more preferably 1.5 or more and 4.5 or less, and even more preferably 2.5 or more and 4.5 or less. When the M / Ti molar ratio of the mixture is 1.0 or more and 5.0 or less, the silicotitanate composition can be efficiently obtained.

[0065] The silicotitanate gel contains niobium. The silicotitanate gel containing niobium can be obtained by at least one of the following methods: mixing an inorganic titanium compound, an inorganic silicon compound, water, an alkali metal hydroxide and a niobium source, or adding a niobium source to the silicotitanate gel.

[0066] The niobium source is preferably at least one of the group consisting of metals, alloys and compounds containing niobium.The niobium compound can be at least one of the group consisting of hydroxides, chlorides, nitrates and sulfates containing niobium.In order to further improve the Cs adsorption properties of the silicotitanate composition, the niobium source can be at least one of the compounds containing niobium, hydroxides or nitrates containing niobium, or even hydroxides of niobium.

[0067] The method for producing the silicotitanate composition used in the present invention includes a crystallization step of crystallizing a silicotitanate gel having the following molar ratio:

[0068] Si / Ti molar ratio: 0.5 or more, 2.0 or less H2O / Ti molar ratio: 20 or more and 100 or less, preferably 50 or more and 100 or less, more preferably 50 or more and 90 or less M / Ti molar ratio: 1.0 or more, 5.0 or less Nb / Ti molar ratio: 0.36 or more and 0.65 or less, preferably 0.36 or more and 0.55 or less or Si / Ti molar ratio: 0.5 or more, 1.29 or less H2O / Ti molar ratio: over 100, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less Nb / Ti molar ratio: 0.36 or more, 0.65 or less or Si / Ti molar ratio: 1.40 or more, 2.0 or less H2O / Ti molar ratio: over 100, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less Nb / Ti molar ratio: 0.36 or more, 0.65 or less In the crystallization step, the silicotitanate composition used in the present invention can be obtained by crystallizing the silicotitanate gel having such a mixed molar ratio. The silicotitanate gel crystallized in the crystallization step preferably has the following composition.

[0069] Si / Ti molar ratio: 0.5 or more, 1.29 or less H2O / Ti molar ratio: over 100, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less Nb / Ti molar ratio: 0.45 or more, 0.65 or less or Si / Ti molar ratio: 1.40 or more, 2.0 or less H2O / Ti molar ratio: over 100, 150 or less M / Ti molar ratio: 1.0 or more, 5.0 or less Nb / Ti molar ratio: 0.45 or more, 0.65 or less This allows the silicotitanate gel to crystallize in a shorter time.

[0070] The silicotitanate gel is crystallized to obtain a silicotitanate composition.

[0071] In the crystallization step, the silicotitanate gel obtained by mixing inorganic titanium compound, inorganic silicon compound, water and alkali metal hydroxide is crystallized. That is, in the method for producing the silicotitanate composition, not only does it use a silicon source and a titanium source that are not hazardous or deleterious, but it also does not use a structure-directing agent. The structure-directing agent is usually an expensive compound. By using the method for producing the silicotitanate composition that does not use a structure-directing agent, it is possible to produce the silicotitanate composition more cheaply.

[0072] The crystallization temperature may be 150° C. or higher and 230° C. or lower, preferably 160° C. or higher and 220° C. or lower, and more preferably 170° C. or higher and 200° C. or lower. If the crystallization temperature is 150° C. or higher, the crystallinity of the resulting silicotitanate tends to be high. If the crystallization temperature is 230° C. or lower, it is a temperature sufficient for using a general-purpose reaction vessel or the like.

[0073] The crystallization time may be 24 hours or more and 120 hours or less. If the crystallization time is 24 hours or more, the crystallinity of the silicotitanate contained in the obtained silicotitanate composition tends to be high. On the other hand, if the crystallization time is 120 hours or less, a silicotitanate composition having sufficient Cs or Sr adsorption properties can be obtained.

[0074] The method for producing the silicotitanate composition used in the present invention can obtain the silicotitanate composition by crystallizing the silicotitanate gel in the crystallization step. Furthermore, the method for producing the silicotitanate composition used in the present invention may include at least one of the steps of cooling, filtering, washing, and drying the silicotitanate composition, which is the crystallized product obtained by the crystallization.

[0075] When the crystallized silicotitanate composition is cooled, the cooling conditions are not particularly limited, but examples thereof include cooling in a heating furnace at 10° C. / min, or removing from the heating furnace and forcibly or naturally cooling.

[0076] When filtering the crystallized silicotitanate composition, any filtering method can be used. For example, filtering using a Nutsche filter or a filter such as a belt filter can be used. In filtering using a filter, it is preferable to use a filter with an opening of about 1 μm.

[0077] When washing the crystallized silicotitanate composition, pure water of 5 to 10 times the weight of the silicotitanate composition can be used as washing water.Furthermore, it is preferable to use the pure water as washing water, which is hot water at 60°C to 90°C.The silicotitanate composition can be washed by mixing the pure water with the silicotitanate composition.

[0078] When drying the crystallized silicotitanate composition, the silicotitanate composition may be dried in the air at 50° C. or higher and 120° C. or lower, or further at 70° C. or higher and 90° C. or lower. If the silicotitanate composition aggregates after drying, it may be appropriately disintegrated using a mortar, a grinder, or the like.

[0079] By undergoing these steps after crystallization, the silicotitanate composition can be made into a powder. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0081] (Powder X-ray diffraction measurement) The XRD pattern of the sample was measured using an X-ray diffractometer (horizontal sample type multipurpose X-ray diffractometer: Ultima IV, manufactured by Rigaku Co., Ltd.) under the following measurement conditions.

[0082] Radiation source: CuKα radiation (λ=1.5405Å) Tube voltage: 40kV Tube current: 40mA Detector: High-speed one-dimensional X-ray detector D / teX Ultra2 Measurement mode: Continuous Starting angle: 3.0° End angle: 43.0° Sampling width: 0.020° Scan speed: 40° / min Divergence slit: 1.0° Divergence vertical limit slit: 10mm The sitinakite structure was identified by comparing the obtained XRD pattern with the XRD peaks of silicotitanate with sitinakite structure described on the reference website.

[0083] (Compositional Analysis of Silicotitanate Composition) The composition of the crystallized material was analyzed by a general ICP method using an ICP-AES (instrument name: OPTIMA3000DV, manufactured by PERKIN-ELMER).

[0084] (Measurement of Sr and Cs ion concentrations) As the medium to be treated, a metal ion-containing aqueous solution (hereinafter also referred to as "simulated seawater") containing at least one of Cs and Sr and having a composition similar to that of seawater was prepared, and the aqueous solution was subjected to an adsorption treatment. The Sr ion concentration in the aqueous solution was appropriately diluted and measured by the ICP method. An ICP-AES (apparatus name: OPTIMA3000DV, manufactured by PERKIN-ELMER) was used for the measurement.

[0085] In addition, the Cs concentration in the aqueous solution was measured using an ICP-MASS (apparatus name: NExION300S, manufactured by PERKIN-ELMER).

[0086] (Cs, Sr ion exchange capacity) The ion exchange capacity of each metal after adsorption treatment was calculated using the following formula (2).

[0087] Ion exchange capacity = (C.-C) / C. ×100 (2) C: Metal ion concentration (ppm) in the metal ion-containing aqueous solution before adsorption treatment C: Metal ion concentration in the metal ion-containing aqueous solution at adsorption equilibrium (ppm) Example 1 20 g of sodium silicate (SiO2; 29.1% by weight) and 71 g of an aqueous solution of titanium oxysulfate (TiO2; 7.8% by weight) were mixed and washed to obtain an amorphous silicotitanate gel having the following composition.

[0088] Si / Ti molar ratio=1.40 Na / Ti molar ratio=0.54 To the obtained amorphous silicotitanate gel, 10 g of niobium hydroxide powder (Nb2O5 equivalent: 72.0 wt%), 20 g of sodium hydroxide aqueous solution (NaOH; 48.0 wt%), and pure water were added to obtain a slurry-like Nb-containing amorphous silicotitanate gel having the following composition.

[0089] Si / Ti molar ratio=1.46 Na / Ti molar ratio=4.00 Nb / Ti molar ratio=0.58 H2O / Ti molar ratio = 112 The Nb-containing amorphous silicotitanate gel was charged into a stainless steel autoclave (product name: KH-02, manufactured by HIRO COMPANY) while stirring, and heated at 180° C. for 48 hours to crystallize the amorphous silicotitanate gel and obtain a crystallized product.

[0090] The pressure during crystallization was 0.8 MPa, which corresponds to the water vapor pressure at 180° C. The crystallized product after crystallization was cooled, filtered, washed, and dried to obtain a silicotitanate composition. The composition of the obtained silicotitanate composition was as follows.

[0091] Si / Ti molar ratio=0.95 Na / Ti molar ratio=0.67 Nb / Ti molar ratio=0.58 As a result of the XRD measurement, it was confirmed that the obtained silicotitanate composition had the X-ray diffraction angle and diffraction peak intensity ratio shown in Table 3. The XRD pattern is shown in Figure 1. As a result of comparing the obtained XRD pattern with the XRD peaks listed in the reference HP, it was confirmed that the obtained silicotitanate composition contains S-type silicotitanate and V-type silicotitanate.

[0092] [Table 3] The selective adsorption characteristics of the obtained silicotitanate composition (adsorbent) for Sr and Cs was evaluated using simulated seawater containing Sr and Cs as the medium to be treated. As the simulated seawater, NaCl, MgCl2, CaCl2, Na2SO4, KCl, a Sr standard solution, and a Cs standard solution were used to prepare an aqueous solution containing the following composition.

[0093] Na: 870 ppm by weight (derived from NaCl) Mg: 118 ppm by weight Ca: 41 ppm by weight Na: 126 ppm by weight (derived from Na2SO4) K: 32 ppm by weight Cs: 1 ppm by weight Sr: 1 ppm by weight (Here, the total concentration of Na was 996 ppm by weight.) 0.05g of the obtained silicotitanate composition (adsorbent) was added to 1L of simulated seawater, and the simulated seawater was stirred at 25℃ and 800 rpm for 24 hours to evaluate the Sr and Cs adsorption properties of the silicotitanate composition (adsorbent). Note that the silicotitanate composition (adsorbent) was heated in air at 100℃ for 1 hour as a pretreatment.

[0094] After the evaluation of the adsorption characteristics, the Cs concentration in the simulated seawater was 0.020 ppm by weight, and the Sr concentration was 0.40 ppm by weight. From this, the exchange capacities of Cs and Sr were as follows:

[0095] Cs exchange capacity: 98% Sr exchange capacity: 60% It was confirmed that the silicotitanate composition (adsorbent) has a high selective adsorption capacity for Cs and Sr, and can be used as an adsorbent for both Cs and Sr.

[0096] 2 g of the silicotitanate composition (adsorbent) was placed in a crucible and fired in an electric furnace at 600° C. for 3 hours.

[0097] As a result of the XRD measurement, the XRD pattern of the silicotitanate composition (adsorbent) after calcination is shown in FIG.

[0098] The peak at 11.3±0.5°, which is the main peak of S-type silicotitanate, had disappeared and was not confirmed. The peak at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, had disappeared and was not confirmed. It was confirmed that the crystal structures of S-type silicotitanate and V-type silicotitanate were not maintained and they had become amorphous.

[0099] The Sr selective adsorption properties of the silicotitanate composition (adsorbent) after calcination at 600°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption properties was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0100] Sr exchange capacity: 0% This confirmed that the ion exchange performance of the silicotitanate composition (adsorbent) was lost after firing, and ion desorption due to back exchange did not occur, allowing the adsorbate to be immobilized.

[0101] The XRD peak intensity ratio and Sr exchange capacity are shown in Table 4.

[0102] [Table 4] Therefore, it was demonstrated that the silicotitanate composition (adsorbent) can be stabilized and disposed of by calcining at 600°C.

[0103] Example 2 A calcined silicotitanate composition (adsorbent) was obtained in the same manner as in Example 1, except that the silicotitanate composition (adsorbent) was calcined at 800° C. for 3 hours.

[0104] As a result of the XRD measurement, the XRD pattern of the silicotitanate composition (adsorbent) after calcination is shown in FIG.

[0105] The peak at 11.3±0.5°, which is the main peak of S-type silicotitanate, disappeared and was not confirmed. The peak at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, disappeared and was not confirmed. It was confirmed that the crystal structure of S-type silicotitanate and V-type silicotitanate was not maintained and became amorphous. In addition, it was confirmed that the peak thought to be cristobalite, a stable silica compound, at 22.5±0.5°, which was a small amount in Example 1, was greatly developed.

[0106] The Sr selective adsorption characteristics of the silicotitanate composition (adsorbent) after calcination at 800°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption characteristics was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0107] Sr exchange capacity: 0% This confirmed that the ion exchange performance of the silicotitanate composition (adsorbent) was lost after firing, and ion desorption due to back exchange did not occur, allowing the adsorbate to be immobilized.

[0108] The XRD peak intensity ratio and Sr exchange capacity are shown in Table 4.

[0109] Therefore, it was demonstrated that the silicotitanate composition (adsorbent) can be stabilized and disposed of by calcining at 800°C.

[0110] Example 3 A calcined silicotitanate composition (adsorbent) was obtained in the same manner as in Example 1, except that the silicotitanate composition (adsorbent) was calcined at 990° C. for 3 hours.

[0111] As a result of the XRD measurement, the XRD pattern of the silicotitanate composition (adsorbent) after calcination is shown in FIG.

[0112] The peak at 11.3±0.5°, which is the peak of S-type silicotitanate, disappeared and was not confirmed. The peak at 27.5±0.5°, which is the peak of V-type silicotitanate, disappeared and was not confirmed. It was confirmed that the crystal structure of S-type silicotitanate and V-type silicotitanate was not maintained and was amorphous. In addition, it was confirmed that the peak thought to be cristobalite, a stable silica compound, at 22.5±0.5°, which was a very small amount in Example 1, was greatly developed. It was confirmed that no significant structural change occurred after the heat treatment at 800°C and that it was stable against heat.

[0113] The Sr selective adsorption characteristics of the silicotitanate composition (adsorbent) after calcination at 990°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption characteristics was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0114] Sr exchange capacity: 0% This confirmed that the ion exchange performance of the silicotitanate composition (adsorbent) was lost after firing, and ion desorption due to back exchange did not occur, allowing the adsorbate to be immobilized.

[0115] The XRD peak intensity ratio and Sr exchange capacity are shown in Table 4.

[0116] Therefore, it was demonstrated that the silicotitanate composition (adsorbent) can be stabilized and disposed of by calcining at 990°C.

[0117] Comparative Example 1 A calcined silicotitanate composition (adsorbent) was obtained in the same manner as in Example 1, except that the silicotitanate composition (adsorbent) was calcined at 400° C. for 3 hours.

[0118] As a result of the XRD measurement, the XRD pattern of the silicotitanate composition (adsorbent) after calcination is shown in FIG.

[0119] The peak intensity at 11.3±0.5°, which is the main peak of S-type silicotitanate, was 63% of the peak intensity at 11.3° of the silicotitanate composition before calcination. The peak intensity at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, was 48% of the peak intensity at 11.3° of the silicotitanate composition before calcination. Although the peak intensity decreased, it was confirmed that the crystal structures of S-type silicotitanate and V-type silicotitanate were maintained.

[0120] The Sr selective adsorption characteristics of the silicotitanate composition (adsorbent) after calcination at 400°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption characteristics was 0.70 ppm by weight. From this, the Sr exchange capacity was as follows.

[0121] Sr exchange capacity: 30% From this, it was confirmed that calcination at 400°C did not sufficiently decrystallize and stabilize the silicotitanate composition (adsorbent), the ion exchange performance of the silicotitanate composition after calcination was not lost, ions were desorbed due to back exchange, and the adsorbate was not completely fixed.

[0122] The XRD peak intensity ratio and Sr exchange capacity are shown in Table 4.

[0123] Therefore, it was shown that the silicotitanate composition (adsorbent) cannot be sufficiently stabilized by baking at 400°C, and therefore cannot be discarded.

[0124] Example 4 100g (anhydrous equivalent) of the silicotitanate composition of Example 1 was put into a mixer (product name: Model 2P-03, manufactured by Primix) together with 12g (anhydrous equivalent) of an inorganic binder (colloidal silica, product name: Snowtex, manufactured by Nissan Chemical Industries Co., Ltd.) and 6g (anhydrous equivalent) of a thickener (product name: Sunrose F-20HC, manufactured by Nippon Paper Industries Co., Ltd.) and kneaded. The mixture was then put into a small single-screw extruder (product name: MG-55-1, manufactured by Dalton) and extruded at a rotation speed of 25 rpm using various dies (1.0 mmφ dome type) to form into a cylindrical shape. The mixture was then baked at 110°C for 24 hours to obtain a silicotitanate molded body.

[0125] The selective adsorption characteristics of Sr and Cs of the obtained silicotitanate compact (adsorbent) were evaluated using simulated seawater containing Sr and Cs as the medium to be treated. As the simulated seawater, NaCl, MgCl2, CaCl2, Na2SO4, KCl, Sr standard solution, and Cs standard solution were used to prepare an aqueous solution containing the following composition.

[0126] Na: 870 ppm by weight (derived from NaCl) Mg: 118 ppm by weight Ca: 41 ppm by weight Na: 126 ppm by weight (derived from Na2SO4) K: 32 ppm by weight Cs: 1 ppm by weight Sr: 1 ppm by weight (Here, the total concentration of Na was 996 ppm by weight.) 0.05g of the obtained silicotitanate compact (adsorbent) was added to 1L of simulated seawater, and the simulated seawater was stirred at 25℃ and 800 rpm for 24 hours to evaluate the Sr and Cs adsorption properties of the silicotitanate compact (adsorbent). The silicotitanate compact (adsorbent) was pretreated by heating it in air at 100℃ for 1 hour.

[0127] After the evaluation of the adsorption characteristics, the Cs concentration in the simulated seawater was 0.09 ppm by weight, and the Sr concentration was 0.45 ppm by weight. From this, the exchange capacities of Cs and Sr were as follows:

[0128] Cs exchange capacity: 91% Sr exchange capacity: 55% The ion exchange performance of the silicotitanate molded body (adsorbent) was evaluated.

[0129] 2 g of the silicotitanate molded body (adsorbent) was placed in a crucible and fired in an electric furnace at 600° C. for 3 hours.

[0130] As a result of the XRD measurement, the XRD pattern of the sintered silicotitanate molded body (adsorbent) is shown in FIG.

[0131] The peak at 11.3±0.5°, which is the main peak of S-type silicotitanate, disappeared and was not confirmed. The peak at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, disappeared and was not confirmed. It was confirmed that the crystal structure of S-type silicotitanate and V-type silicotitanate was not maintained and they were made amorphous.

[0132] The Sr selective adsorption properties of the silicotitanate molded body (adsorbent) after calcination at 600°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption properties was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0133] Sr exchange capacity: 0% This confirmed that the ion exchange capacity of the sintered silicotitanate molded body (adsorbent) was lost, ion desorption due to back exchange did not occur, and the adsorbate could be immobilized.

[0134] The XRD peak intensities and Sr exchange capacities are shown in Table 4.

[0135] The XRD peak intensity ratio was calculated by taking the peak intensity at 11.3° for the product fired at 110° C. as 100 and calculating the peak intensities at 2θ=11.3°, 27.8°, and 22.5° for Example 4.

[0136] Therefore, it was shown that the silicotitanate molded body (adsorbent) can be stabilized and disposed of by calcining at 600°C.

[0137] Example 5 A calcined silicotitanate molded body (adsorbent) was obtained in the same manner as in Example 4, except that the silicotitanate molded body (adsorbent) was calcined at 800° C. for 3 hours.

[0138] As a result of the XRD measurement, the XRD pattern of the sintered silicotitanate molded body (adsorbent) is shown in FIG.

[0139] The peak at 11.3±0.5°, which is the main peak of S-type silicotitanate, disappeared and was not confirmed. The peak at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, disappeared and was not confirmed. It was confirmed that the crystallization structure of S-type silicotitanate and V-type silicotitanate was not maintained and was made amorphous. It was also confirmed that cristobalite, a stable silica compound, was produced.

[0140] The Sr selective adsorption properties of the silicotitanate molded body (adsorbent) after calcination at 800°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption properties was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0141] Sr exchange capacity: 0% This confirmed that the ion exchange capacity of the sintered silicotitanate molded body (adsorbent) was lost, ion desorption due to back exchange did not occur, and the adsorbate could be immobilized.

[0142] The XRD peak intensities and Sr exchange capacities are shown in Table 4.

[0143] The XRD peak intensity ratio was calculated by taking the peak intensity at 11.3° for the product fired at 110° C. as 100 and calculating the peak intensities at 2θ=11.3°, 27.8°, and 22.5° for Example 5.

[0144] Therefore, it was shown that the silicotitanate molded body (adsorbent) can be stabilized and disposed of by calcining at 800°C.

[0145] Example 6 A calcined silicotitanate molded body (adsorbent) was obtained in the same manner as in Example 4, except that the silicotitanate molded body (adsorbent) was calcined at 990° C. for 3 hours.

[0146] As a result of the XRD measurement, the XRD pattern of the sintered silicotitanate molded body (adsorbent) is shown in FIG.

[0147] The peak at 11.3±0.5°, which is the main peak of S-type silicotitanate, disappeared and was not confirmed. The peak at 27.5±0.5°, which is a part of the peak of V-type silicotitanate, disappeared and was not confirmed. It was confirmed that the crystallization structure of S-type silicotitanate and V-type silicotitanate was not maintained and was made amorphous. It was also confirmed that cristobalite was generated in Example 4. It was confirmed that no significant structural change occurred after the heat treatment at 800°C and that it was stable against heat.

[0148] The Sr selective adsorption properties of the silicotitanate molded body (adsorbent) after calcination at 990°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption properties was 1.00 ppm by weight. From this, the Sr exchange capacity was as follows.

[0149] Sr exchange capacity: 0% This confirmed that the ion exchange capacity of the sintered silicotitanate molded body (adsorbent) was lost, ion desorption due to back exchange did not occur, and the adsorbate could be immobilized.

[0150] The XRD peak intensities and Sr exchange capacities are shown in Table 4.

[0151] The XRD peak intensity ratio was calculated by taking the peak intensity at 11.3° for the product fired at 110° C. as 100 and calculating the peak intensities at 2θ=11.3°, 27.8°, and 22.5° for Example 6.

[0152] Therefore, it was shown that the silicotitanate molded body (adsorbent) can be stabilized and disposed of by calcining at 990°C.

[0153] Comparative Example 2 A calcined silicotitanate molded body (adsorbent) was obtained in the same manner as in Example 4, except that the silicotitanate molded body (adsorbent) was calcined at 400° C. for 3 hours.

[0154] As a result of the XRD measurement, the XRD pattern of the sintered silicotitanate molded body (adsorbent) is shown in FIG.

[0155] The XRD peak intensity ratio was calculated by taking the peak intensity at 11.3° for the product fired at 110°C as 100 and calculating the peak intensities at 2θ=11.3°, 27.8°, and 22.5° for Comparative Example 2.

[0156] The peak intensity at 11.3±0.5°, which is the main peak of S-type silicotitanate, was 56% of the peak at 11.3° of the silicotitanate molded product before calcination. The peak intensity at 27.5±0.5°, which is a part of the V-type silicotitanate peak, was 29% of the peak at 11.3° of the silicotitanate molded product calcined at 110°C. Although the peak intensity decreased, it was confirmed that the crystal structures of S-type silicotitanate and V-type silicotitanate were maintained.

[0157] The Sr selective adsorption properties of the silicotitanate molded body (adsorbent) after calcination at 400°C were evaluated. The Sr concentration in the simulated seawater after the evaluation of the adsorption properties was 0.84 ppm by weight. From this, the Sr exchange capacity was as follows.

[0158] Sr exchange capacity: 16% From this, it was confirmed that calcination at 400°C was insufficient to amorphize and stabilize the silicotitanate molded body (adsorbent), the ion exchange capacity of the silicotitanate molded body (adsorbent) was not lost after calcination, ions were released due to back exchange, and the adsorbate was not completely fixed.

[0159] The XRD peak intensities and Sr exchange capacities are shown in Table 4.

[0160] Therefore, it was shown that the silicotitanate molded body (adsorbent) cannot be sufficiently stabilized by firing at 400°C, and therefore cannot be discarded. [Industrial Applicability]

[0161] The present invention provides a method for the disposal of adsorbents that can be safely produced using inexpensive raw materials and that can use a general-purpose autoclave. The present invention makes it possible to efficiently treat adsorbents that have adsorbed harmful ions such as Cs and Sr that coexist in seawater, groundwater, and contaminated water.

Claims

1. Heating the adsorbent having adsorbed the adsorbent at a temperature of 500° C. or more and 990° C. or less; The adsorbent comprises a silicotitanate composition; The silicotitanate composition comprises at least one of a silicotitanate having a sitinakite structure and a silicotitanate having a vinogradovite structure; The method for waste treatment of an adsorbent, characterized in that, in an XRD pattern of the adsorbent after heating at a temperature of 500° C. or more and 990° C. or less, the XRD peak intensity ratio at 2θ=27.5±0.5° is less than 29%.

2. 2. The method for waste treatment of an adsorbent according to claim 1, wherein the adsorbent has an XRD peak intensity ratio at 2θ=11.3±0.5° in an XRD pattern after heating at a temperature of 500° C. or more and 990° C. or less of the adsorbent, of less than 56%.

3. 3. The method for waste treatment of an adsorbent according to claim 1, wherein the ion exchange capacity of the adsorbent after the heating step is 10% or less.

4. 4. The method for waste treatment of an adsorbent according to claim 1, wherein the adsorbent contains a silicotitanate molded body containing the silicotitanate composition and an inorganic binder.

5. The method for waste disposal of an adsorbent according to any one of claims 1 to 4, characterized in that the silicotitanate composition contains niobium and a silicotitanate having a sitinakite structure, and has diffraction peaks at least at 2θ=27.8±0.5° and 2θ=29.4±0.5°.

6. The method for waste disposal of an adsorbent according to any one of claims 1 to 5, characterized in that the silicotitanate composition has the following molar ratio and has the 2θ and peak intensity ratio shown in Table 1. Si / Ti molar ratio: 0.40 or more, 2.0 or less M / Ti molar ratio: 0.50 or more and 4.0 or less Nb / Ti molar ratio: 0.35 or more, 0.60 or less (M is one alkali metal selected from the group consisting of Li, Na, and K). 【Table 1】 (In Table 1, the XRD peak intensity ratio refers to the ratio of peak heights.)

7. 7. The method for waste treatment of an adsorbent according to claim 1, wherein the adsorbate is strontium or cesium.

Citation Information

Patent Citations

  • Method for adsorbing at least one of cesium and strontium using composition containing silicotitanate having sitinakite structure

    JP2017170440A

  • Method for disposing adsorbent

    JP2021133362A

  • Method for manufacturing solidified body of radioactive waste

    WO2017222000A1

  • Method for measuring tsh

    JP1986057857A

  • Method for manufacturing solidified radioactive waste

    JP6557416B2

Cited By

  • Method for utilizing zeolite related to PFAS and apparatus directly used for its implementation, and method for manufacturing amorphous materials related to PFAS and apparatus directly used for its implementation.

    JP7900802B1